1996
DOI: 10.1016/0360-5442(96)00025-4
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic version of the dynamic linear programming model MESSAGE III

Abstract: All rights resen ecl. No pa.rt of this publica ti o n m a.v be re pro duced o r tra ns mitted in a.ny form or by a n~' mea.ns. elec t ronic o r mec ha ni ca l. includin g photoco py, recordin g, or any inform a.t.ion s to rage o r retrie val syste m , \\·it ho ut pe rmissio n in writin g fr om t he co py right hold er. Abstract-This paper introduces an approach to modeling the uncertainties concerning future characteristics of energy technologies within the framework of long-term dynamic linear programming mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 12 publications
0
50
0
Order By: Relevance
“…What is therefore required as an addition to this initial experiment is the further expansion of the approach to deal with uncertainties concerning the success of new technologies, as well as the uncertainties concerning the development paths that technology performance takes. An initial step in this direction has been taken by introducing the uncertainties of future technology performance as such into the model formulation [48]. Early experiments with the stochastic version of MESSAGE have shown that, if the uncertainties concerning future technology performance are incorporated, the model tends to spread risk over more technologies.…”
Section: Discussionmentioning
confidence: 99%
“…What is therefore required as an addition to this initial experiment is the further expansion of the approach to deal with uncertainties concerning the success of new technologies, as well as the uncertainties concerning the development paths that technology performance takes. An initial step in this direction has been taken by introducing the uncertainties of future technology performance as such into the model formulation [48]. Early experiments with the stochastic version of MESSAGE have shown that, if the uncertainties concerning future technology performance are incorporated, the model tends to spread risk over more technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The first line of objective function (14) is the same as that of objective function (9), and in the Messner et al 1996). …”
Section: The Modelmentioning
confidence: 99%
“…Relevant references here are Messner et al (1996), Krey et al (2007), Grubler and Gritsevskyi (2002), and Gritsevskyi and Nakicenovic (2000). These studies not only focus on stochastic energy prices, but also on technological uncertainties, in particular uncertain future technology costs and how these respond to alternative innovation and investment strategies (i.e.…”
Section: Box Real Options Theorymentioning
confidence: 99%